A fitting problem: Standardising shoe fit standards to reduce related diabetic foot ulcers. (August 2019) - Jones, Petra J.; Bibb, Richard J.; Davies, Melanie J.; Khunti, Kamlesh; McCarthy, Matthew; Fong, Daniel T.P.; Webb, David
Abstract: Aims: Incorrectly fitting shoes are implicated in callus formation and a significant proportion of diabetic foot ulcers, yet remain surprisingly prevalent. We review the current shoe fit guidelines for consistency and discuss ways in which technology may assist us in standardising methods of footwear assessment. Methods: Narrative review. Results: Incorrectly fitted shoes are implicated in the development of some diabetic foot ulcers yet surprisingly there's no consensus on shoe fit, despite substantial spending on prescription footwear. Suggested toe gaps vary from 6 to 20 mm and measurement methods also vary from Brannock Devices and callipers to manual measurement. Conclusions: To prevent fit-related foot ulceration, we need to standardise our biomechanical definition of fit. Future research should (1) evaluate the potential use of 3D scanning technology to provide a standardised means of capturing foot morphology; (2) develop a working biomechanical definition of fit, including toe gap through the identification of key physiological markers that capture and predict dynamic foot shape changes during different physical activities and body weight loading conditions; and (3) determine whether changes in dynamic foot shape of those with diabetes differs from those without, impacting on their shoe fitting needs, potentially necessitating specialist footwear at an earlier stage to avoid ulceration.